PENGENALAN ANALISIS MEDIA DAN JEJARING SOSIAL SEBAGAI UPAYA PENINGKATAN LITERASI DIGITAL SISWA SMAN 3 KABUPATEN TANGERANG - Yukianti, Chiara Rizka; Angkasa, Adhelia; Lavenia; Willyanto, Vinnie; Puspitasari, Rani; Mawardi, Viny Christanti (Jurnal Serina Abdimas, 2024)
Internet penetration has dramatically changed the way individuals communicate and interact. Social media has become an important tool for interacting and sharing information, especially in Indonesia with more than 86% of its users. This phenomenon presents both opportunities and challenges, including the risk of privacy violations, the spread of misinformation, and cyberbullying. Therefore, education regarding the wise and responsible use of social media is important. Social media analysis (SMA) and social network analysis (SNA) are effective tools for increasing public understanding of the impact of social media. SMA is used to collect and analyze social media data, while SNA understands social interactions in society. With deeper understanding, social media users can make more informed decisions. Seminar and training activities for students at SMAN 3 Tangerang Regency aim to provide education to overcome students' limited knowledge about social media and social network analysis. Through two-hour seminars and training, students will learn about the benefits and uses of social media and web analytics in their daily lives. The evaluation results show that the material was delivered well and students reported that the activity was useful. They felt good and enjoyed themselves, especially during the fun learning sessions, quizzes and demonstrations of the use of social media analysis tools. This activity gives students a deeper understanding of social media and social network analysis, helping students make better decisions and develop more effective strategies in the digital world. This PKM activity will have a positive impact on their ability to wisely use social media and understand social dynamics in the digital era.